2009
DOI: 10.1016/j.compchemeng.2008.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing control based on output feedback

Abstract: In the framework of process optimization, the use of measurements to compensate the effect of uncertainty has re-emerged as an active area of research. One of the ideas therein is to adapt the inputs in order to track the active constraints and push certain sensitivities to zero. In perturbation-based optimization, the sensitivities are evaluated by perturbation of the inputs and measurement of the cost function, which can be experimentally time consuming. However, since more measurements (typically the output… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 14 publications
0
48
0
Order By: Relevance
“…It has been shown that a particular choice of CVs leads to an estimation of the cost gradient 13 , which is precisely the focus of NEC. Although the two approaches attempt to solve the same static optimization problem, they are still sometimes seen as being different 13 , which is probably due to the fact that they were introduced with different types of measurements, namely, at steady state for NEC 11 and in the transient for SOC 9 . By presenting the two approaches on the same footing, this paper shows that they are indeed very similar and, in fact, the two methods can be made strictly equivalent through appropriate tuning.…”
Section: Control Methods -In Techniques Such As Nco Trackingmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that a particular choice of CVs leads to an estimation of the cost gradient 13 , which is precisely the focus of NEC. Although the two approaches attempt to solve the same static optimization problem, they are still sometimes seen as being different 13 , which is probably due to the fact that they were introduced with different types of measurements, namely, at steady state for NEC 11 and in the transient for SOC 9 . By presenting the two approaches on the same footing, this paper shows that they are indeed very similar and, in fact, the two methods can be made strictly equivalent through appropriate tuning.…”
Section: Control Methods -In Techniques Such As Nco Trackingmentioning
confidence: 99%
“…The first method, neighboring-extremal control (NEC), implements first-order optimality corrections using state feedback 10 . It has been shown that NEC is a first-order approximation to gradientbased optimization 11 . The second method is self-optimizing control (SOC) based on the null-space method, which proposes to determine CVs that ensure marginal optimality loss when maintained at their nominal optimal values 9,12 .…”
Section: Control Methods -In Techniques Such As Nco Trackingmentioning
confidence: 99%
See 2 more Smart Citations
“…Again, the performance of such an approach will generally decrease when the number of inputs and plant constraints increases. Alternatively, gradient estimates can be obtained by using (i) a variational analysis of the modeled cost and constraint functions to obtain the gradients in terms of the inputs and outputs, and (ii) plant measurements to compute the gradient values at the current iteration 26 . This approach can lead to perfect gradient estimates provided the model uncertainty is of parametric nature and the identity of the uncertain parameters is known.…”
Section: Gradient Estimationmentioning
confidence: 99%